Treatment of quick-service restaurant wastewater by electrocoagulation effects of current density, electrolysis time, and charge loading on pollutant removal and energy consumption - Perez, Jem Valerie D. (2012)
In this study, electrocoagulation (EC) was applied to treat quick-service restaurant (QSR) wastewater characterized by high organic matter, mainly oil and grease content. The effects of several process parameters including current density, electrolysis time, charge loading, and conductivity on the performance of EC in terms of pollutant removal, power requirement, and electrode material consumption were studied. The wastewater used in the study was obtained from a student canteen in UP Diliman. Experiments were performed in a batch EC reactor with four monopolar aluminum electrodes arranged in a parallel connection. Operating conditions of 30-90 A/m^2 and 10-30 min were investigated. Pollutant removal efficiencies were primarily affected by charge loading. Suspended matter was removed more satisfactorily than dissolved matter. Treatment at a higher current density required shorter electrolysis time for the same percentage level of removal of pollutants , but at the expense of greater electrical energy consumption.The best operating condition that provided minimum values of energy and electrode material consumption per percent of removal of pollutants was determined to be EC treatment using a current density of 30 A/m^2 operated at 30 min. This condition demanded only 0.875 kWh/m^3 and 0.049 kg Al/m^3 of energy and electrode material, respectively. Maximum removal percentages of 92.82% color, 98.41% turbidity, 80.57% total COD 67.16% dissolved COD, 92.95% TSS, and 88.95% FOG were achieved when operated at 90 A/m^2 for 30 min. Wastewater conductivity had no significant effect on pollutant removal, but significantly reduced voltage and energy requirements. Overall, the data collected proved that EC can be successfully applied to treat QSR wastewater in the Philippines. IT can be incorporated as post-treatment process for grease traps, or as pre-treatment process for biological methods.
Thesis (M.S. Chemical Engineering)--University of the Philippines, Diliman.
Keywords: Electrocoagulation